2018
DOI: 10.1128/msystems.00220-17
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Bacterial Global Modulators: Role of a Novel H-NS Paralogue in the Enteroaggregative Escherichia coli Strain 042

Abstract: Global regulators such as H-NS play key relevant roles enabling bacterial cells to adapt to a changing environment. H-NS modulates both core and horizontally transferred (HGT) genes, but the mechanism by which H-NS can differentially regulate these genes remains to be elucidated. There are several instances of bacterial cells carrying genes that encode homologues of the global regulators. The question is what the roles of these proteins are. We noticed that the enteroaggregative E. coli strain 042 carries a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 50 publications
1
25
0
Order By: Relevance
“…), indicated that, although H‐NS marginally represses both promoters, AggR still substantially activates transcription in the absence of H‐NS. Consistent with this, a recent transcriptomic analysis in EAEC 042 indicated that neither afaB nor aafD were derepressed by the absence of H‐NS or its homologue H‐NS2 (EC042_2824) (Prieto et al , ). Therefore, we propose that, at the afaB and aafD promoters, AggR primarily activates transcription by directly interacting with RNA polymerase rather than alleviating H‐NS repression.…”
Section: Discussionmentioning
confidence: 69%
“…), indicated that, although H‐NS marginally represses both promoters, AggR still substantially activates transcription in the absence of H‐NS. Consistent with this, a recent transcriptomic analysis in EAEC 042 indicated that neither afaB nor aafD were derepressed by the absence of H‐NS or its homologue H‐NS2 (EC042_2824) (Prieto et al , ). Therefore, we propose that, at the afaB and aafD promoters, AggR primarily activates transcription by directly interacting with RNA polymerase rather than alleviating H‐NS repression.…”
Section: Discussionmentioning
confidence: 69%
“…Histone‐like nucleoid‐structuring protein (H‐NS), one of the global regulators of transcription, plays roles enabling bacterial cells to adapt to a changing environment . H‐NS consists of 137 amino acid residues with oligomerization and DNA‐binding domains.…”
Section: Introductionmentioning
confidence: 99%
“…StpA, Hfp and Sfh (HppH) bind to many of the same chromosomal loci as H-NS in E. coli and Salmonella ( 3 , 27 , 40 ). The DNA binding domain (T110–A117) is 100% conserved within the H-NS clade and largely conserved across the homolog clades (Figure 3D ).…”
Section: Resultsmentioning
confidence: 99%
“…Also problematic is that a mix of manual and automated genome annotations according to top BLAST hits has resulted in H-NS homologs with multiple names in use (e.g. Hfp and HNS2) ( 26 , 40 ), or multiple homologs in a genome all being classified as H-NS. Thus, gene and protein names may not accurately reflect evolutionary and functional relatedness.…”
Section: Introductionmentioning
confidence: 99%